Identifying B2B customer needs with electrification within the industrial sector - Dehn, Ella; Larsson, Louise (My University, 2022)
As the pressure for green solutions increases and the costs for li-ion batteries decrease, producers find more and more viable business cases for its applications. Consequently, li-ion battery producers are entering new markets and engaging with new customers, for example within the industrial sector. Customers in the industrial sector will likely have different needs and face different challenges than those in existing markets, and to understand these is crucial to offer a relevant product. Thus, in order to best support the process of li-ion battery electrification of the industrial sector, it is of interest to understand what needs industrial companies have related to this. The purpose of this study is to investigate what needs and challenges industrial customers face in electrification with li-ion batteries of their machines. The study will also discuss how these needs could be met by digital solutions. The focus will lie on industrial customers within material handling, construction equipment and marine. The study is mainly based on semi-structured interviews with employees at organizations that are, existing or potential, customers to a li-ion battery producer, the case company. The study identifies seven parameters along which li-ion batteries need to perform in order to meet customers needs and challenges. These are productivity, availability, energy density, cost, emission, precision and security. In addition, industrial organizations are challenged to renewing their business model when electrifying their products. Further, there is a vast knowledge gap within industry on li-ion batteries, both with equipment producers and end-users. The study concludes that digital solutions could be used to increase li-ion batteries performance along the identified parameters, but as for business model renewal and knowledge gap, alternative solutions might have a larger impact. However, to outline these solutions in greater detail, further research needs to be conducted.
Keywords: Lithium-ion batteries; energy storage systems; digital solutions; industrial; electrification; technological innovation; complementary assets; organizational adoption; performance parameters; customer needs